TINGKAT SERANGAN PARASIT PADA IKAN MAS (Cyprinus carpio L.) DI KELOMPOK PEMBUDIDAYA IKAN MINA HARAPAN BARU DESA AWANG BANGKAL BARAT KECAMATAN KARANG INTAN - Sri Ramadhana; Bambang S Sihananto; Adi Wahyudi (Chlorophyl, 2025)
This study aims to determine the condition factor of common carp (Cyprinus carpio L.), identify parasitic species, and analyze parasite infestation levels (prevalence) in floating net cages (KJA) at the Mina Harapan Baru fish farming group, Awang Bangkal Barat Village, Karang Intan District. A descriptive, qualitative survey was used. Sampling was conducted three times at seven-day intervals using random sampling on 15 fish. Ectoparasite examination was performed on skin mucus and gills under a microscope. Observed parameters included fish condition factor, parasite species, prevalence, and water quality. Results showed that common carp were infected by seven parasite species: Trichodina sp., Dactylogyrus sp., Oodinium sp., Digenea, Henneguya sp., Epistylis sp., and Gyrodactylus sp. Overall prevalence reached 93.33%, categorized as severe infestation. The highest prevalence occurred in Dactylogyrus sp. (80%) and Digenea (73.33%). Water quality showed temperatures of 26.4–28.8°C, pH 7.91–7.99, DO 2.9–3.0 mg/L, and ammonia 0.5 mg/L. DO and ammonia values were outside optimal ranges, likely triggering high parasite infestation